2016
DOI: 10.1186/s13104-016-1941-6
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric diabetic retinopathy: experience of a tertiary hospital in Ethiopia

Abstract: BackgroundDiabetic retinopathy is one of the micro vascular complications of diabetes mellitus. To date there are no studies that show the magnitude of diabetic retinopathy in the pediatric population of Ethiopia with only very few in Africa. The purpose of this study was to determine the prevalence of diabetic retinopathy in children and adolescents at a tertiary center in Ethiopia.MethodsThis cross-sectional hospital based descriptive study included children aged between 9 and 17 years attending the endocrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 17 publications
1
23
3
Order By: Relevance
“…Moreover, this study found that the cumulative incidence and incidence density rate amon chldren with type 1 DM was lower than compared with findings in Tikur Anbessa Specialized hospital (74.4%) [37] and than that of Tanzania (89.9%) [11], Benin teaching hospital (77.1%) [24], Romania (67%), Taiwan (65%) [36]. The lower cumulative incidence might be explained by the improved diabetes education and prevention programs that have been implemented over the last decades.…”
Section: Discussioncontrasting
confidence: 56%
“…Moreover, this study found that the cumulative incidence and incidence density rate amon chldren with type 1 DM was lower than compared with findings in Tikur Anbessa Specialized hospital (74.4%) [37] and than that of Tanzania (89.9%) [11], Benin teaching hospital (77.1%) [24], Romania (67%), Taiwan (65%) [36]. The lower cumulative incidence might be explained by the improved diabetes education and prevention programs that have been implemented over the last decades.…”
Section: Discussioncontrasting
confidence: 56%
“…12,13 In a study of 86 children with type 1 DM from Ethiopia, 4.7% fulfilled the diagnosis for background DR, using fundus photography through dilated pupils performed by nurses. 13 It is unclear if the photographs were reviewed by an ophthalmologist.…”
Section: Eye Complicationsmentioning
confidence: 99%
“…1 A few reports have raised concern that children of non-Caucasian ancestry may develop ophthalmic complications precociously. [6][7][8][9][10][11] However, only sparse data on the topic is available in children of Abbreviations: BMI, body mass index; CDC, Centre for Disease Control; DR, diabetic retinopathy; DM, diabetes mellitus; kg, kilogram; m, meter; SD, standard deviation; IU, international units African ancestry living in low-resource setting, 12,13 and no study exists in children of Haitian descent. Such data is essential to provide adequate screening and early detection of ocular complications in the goal to avoid the irreversible consequence of visual impairment or blindness.…”
Section: Introductionmentioning
confidence: 99%
“…; Shibeshi et al. ). Moreover, reports on early diabetic CT and screening indicators in children and adolescents are even scarcer.…”
Section: Introductionmentioning
confidence: 97%
“…At present, American Academy of Ophthalmology (AAO) only recommends that detection the levels of blood pressure, blood glucose and HBA1c may reduce the risk of development and progress of DR, and patients with DM undergo annual fundus examination 5 years after initial diagnosis (Taban et al 2009). However, there are few studies on the individual risk factors related to DR in paediatric patients with diabetes and blood glucose, HBA1c and diastolic blood pressure are the only confirmed risk factors (Broe et al 2014;Shibeshi et al 2016). Moreover, reports on early diabetic CT and screening indicators in children and adolescents are even scarcer.…”
Section: Introductionmentioning
confidence: 99%